O ensino médio em instituições escolares do Rio Grande do Sul e a formação humana integral - Dirk, Dirceu Adolfo (2015)
The research had, as broader objective, verify, analyze and identify in school practices, elements indicators of a more focused education for human development and for the integral formation of the student, as suggested by the National Curriculum Guidelines for High School (DCNEM). There was trimming for the Regular High School frequented by young-students who usually just study in private institutions, in federal military schools, in schools linked to federal universities and in state public schools. We opted for the qualitative research approach through documentary analysis of the Brazilian Educational Legislation, the theoretical analysis of integral human formation, at different times and in contemporary times. The data generation on school practices resulted in institutional research sites of private network and of schools federal and the Secretary of State of Education Rio Grande do Sul (SEDUC/RS). Regardless of administrative subordination (private, federal or state), the scholastic institutions draw a thread through which students pass contemplating the protagonist role in their formative paths, in other educational spaces, not necessarily the classroom. Various school activities as complement to learning are developed in the form of extracurricular classes (projects, workshops, programs, study tours, discussions, lectures and actions) and permeates the dimensions the cognitive-intellectual, physical-bodily and artistic-cultural. Many projects and programs seek to develop in students fundamental concepts of citizenship, civic and social responsibility, others, seek to achieve human-social activities through volunteering and solidarity and there, yet, projects focused the area of technology and the world of work. Didactic and pedagogical activities submitted, in this research, can prepare students intellectually to join other steps of study, provide a basis for the world of work and to become active citizens and participants in cultural and political life.